Aktivitas Pembelajaran Menyenangkan mengenai Makanan Bergizi sebagai Upaya Pengenalan Stunting di SDN Ligarmanah - Rachman, Shanti Anggraeni; Qodriyyah, Hasna Fatharani (Universitas Pendidikan Indonesia, 2024)
Stunting has become a particular focus of national health issues. Stunting is when a child is less tall than other children his age, which also affects brain development and metabolic disorders in children. Stunting is caused by a lack of nutritious food intake in children over a long period. This service activity tries to provide stunting education related to healthy food to students at SDN Ligarmanah with fun learning activities. SDN Ligarmanah is one of the schools that has not received sufficient education about stunting, so it is the right target for getting an education. The method used is the compression method, which actively involves students in the learning process, consisting of students from classes 3A, 3B, 4A, and 4B, who were taken using the cluster random sampling technique. This service provides understanding and knowledge to Ligarmanah Elementary School students regarding nutritious food to prevent increased stunting, and the students can display an understanding response to stunting material.